Hubungan Antara Minat Belajar Matematika Dengan Prestasi Belajar Siswa Kelas XI Madrasah Aliyah Negeri Kotabaru - Abi Sara (STKIP Paris Barantai, 2018)
Abstract The purpose of this research is (1) to know the interest of learning mathematics and student achievement of Class XI Madrasah Aliyah Negeri Kotabaru. (2) to know whether or not there is a positive and significant correlation between interest in learning mathematics with student achievement Class XI Madrasah Aliyah Negeri Kotabaru.This type of research is quantitative research, which is a lot of research required to use numbers, ranging from data collection, interpretation of the data, and the appearance of the results. In addition to data in the form of numbers, in quantitative research there is also data in the form of qualitative information. The type of approach used according to the patterns or nature of non-experimental research is correlation research.Correlation research aims to find whether there is a relationship and if there is, how closely the relationship and meaning or not that relationship.The result of the research shows that the students' mathematics learning grade XI Madrasah Aliyah Negeri Kotabaru is categorized in moderate stage with frequency of 46 students and the total percentage is 67,6%. Similarly, the achievement of learning mathematics is also categorized in the middle stage with the frequency of 46 students and the number of percentage of 67.6%. The relationship between interest in learning with high learning achievement of mathematics. It can also be seen from the value of t arithmetic> t table (3,358> 1,997) and significance (0.001 <0.05), then Ho is rejected, meaning that there is a significant relationship between learning interest and learning achievement. Because t arithmetic positive value, then it means interest in learning positive and significant correlation to learning achievement. So in this case it can be concluded that interest in learning is positively and significantly related to the achievement of learning in the students of Class XI Madrasah Aliyah Negeri Kotabaru.Keywords: Interest in Mathematics Learning, Learning Achievement